Composite for secondary battery electrode

The use of fibrous carbon in a controlled dispersion method addresses the challenge of uniform distribution in secondary battery electrodes, enhancing conductivity and battery performance.

JP2025007087AActive Publication Date: 2025-01-17TOYO INK MFG CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023108258
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Existing methods for producing secondary battery electrodes face challenges in uniformly distributing carbon nanotubes due to strong cohesive forces, leading to non-uniform conductive networks and increased electrode resistance, which affects battery performance.

Method used

A composite method using fibrous carbon and active materials is developed, with controlled dispersion and adsorption of fibrous carbon onto the active material, ensuring a uniform conductive network and reduced electrode resistance.

Benefits of technology

The method results in a secondary battery electrode with enhanced conductivity, leading to high-output and long-life nonaqueous electrolyte secondary batteries with improved electron conduction paths and battery characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007087000001_ABST
    Figure 2025007087000001_ABST
Patent Text Reader

Abstract

To provide a composite for a secondary battery electrode having high electrical conductivity by causing fibrous carbon to be uniformly dispersed and adsorbed by a composition method using an active material and fibrous carbon.SOLUTION: In a composite for a secondary battery electrode containing fibrous carbon and an active material, the temperature of the exothermic peak of the fibrous carbon of the composite obtained by thermogravimetry-differential-thermal simultaneous analysis in an oxygen atmosphere is 520°C or less, and the volume resistivity under a load of 20 kN is 100 Ω cm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite for a secondary battery electrode, and an electrode, a secondary battery, and a device each using the composite. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] The electrodes of secondary batteries are prepared by coating a composite slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, etc., on a current collector. A conductive material dispersion liquid in which a conductive material is dispersed in a dispersion medium is prepared, and an active material and a binder resin are added to the conductive material dispersion liquid to prepare a composite slurry, so that the conductive material is uniformly dispersed and contained in the electrode film, and the conductivity of the electrode film can be improved. In order to increase the capacity of secondary batteries, an increase in the ratio of active materials in the electrodes is desired, and carbon nanotubes, which can efficiently form a conductive network even with a small amount as a conductive agent and reduce electrode resistance, are considered promising. On the other hand, in order to achieve low resistance with the addition of a smaller amount of carbon nanotubes, it is effective to use carbon nanotubes with a small average outer diameter and large fiber length. However, these carbon nanotubes have strong cohesive forces, making it difficult to distribute them uniformly in the electrode. In order to efficiently form a conductive network in the electrode and ensure a conductive path to the active material, a method has been proposed in which a composite is used in which a conductive material such as carbon nanotubes is adsorbed onto the surface of the active material in advance.

[0004] Patent Document 1 discloses an example in which a positive electrode active material and acetylene black are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. Patent Document 2 discloses an example of manufacturing a thin-film electrode structure having low resistance and excellent film strength by dispersing and combining an electrode material and single-walled carbon nanotubes using a mill and ultrasonic homogenizer. Furthermore, Patent Document 3 discloses an example in which a positive electrode active material and carbon nanotubes are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-201228 A [Patent Document 2] Patent Publication No. 2022-019738 [Patent Document 3] JP 2017-142997 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the method disclosed in Patent Document 1, a dispersion of acetylene black is used as a conductive assistant, so it is difficult to form an efficient conductive network with a small amount of addition compared to when fibrous carbon is used as a conductive assistant. The method disclosed in Patent Document 2 uses single-walled carbon nanotubes as a conductive assistant, but because it does not contain a dispersant, it is prone to aggregation and requires a large amount of carbon nanotubes to form a conductive network. In the method disclosed in Patent Document 3, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite formation process, and the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in a non-uniform composite, making it difficult to form a uniform conductive network in the electrode.

[0007] In order to solve the above problems, the present invention aims to provide a composite for a secondary battery electrode, which has high conductivity due to the uniform dispersion and adsorption of fibrous carbon by a composite method using an active material and fibrous carbon. [Means for solving the problem]

[0008] The present invention relates to a composite for a secondary battery electrode, comprising fibrous carbon and an active material, and a heat generation peak of the fibrous carbon of the composite obtained by simultaneous thermogravimetry and differential thermal analysis under an oxygen atmosphere. The present invention relates to a composite for a secondary battery electrode, characterized in that the temperature of

[0009] The present invention relates to the composite for a secondary battery electrode according to claim 1, characterized in that the volume resistivity under a load of 20 kN is 100 Ω·cm or less.

[0010] The present invention relates to the above-mentioned composite for a secondary battery electrode, characterized in that the content of fibrous carbon contained in the composite for a secondary battery electrode is 10 mass % or less.

[0011] The present invention relates to the above-mentioned composite for a secondary battery electrode, wherein the fibrous carbon of the composite for a secondary battery electrode has an exothermic peak temperature of 450° C. in an oxygen atmosphere.

[0012] The present invention further relates to the above composite for a secondary battery electrode, which is characterized by containing a binder resin.

[0013] The present invention relates to an electrode for a secondary battery, comprising the above-mentioned composite for a secondary battery electrode.

[0014] The present invention relates to a secondary battery including the above-mentioned secondary battery electrode.

[0015] The present invention relates to a vehicle or device equipped with the secondary battery. Effect of the Invention

[0016] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows an example of a TG curve and a DTA curve in TG-DTA, and a combustion temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.

[0019] In this specification, carbon nanotubes may be referred to as "CNTs." Hydrogenated nitrile rubber may be referred to as "H-NBR," and N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, carbon nanotube dispersions may be simply referred to as "CNT dispersions" or "dispersions." Additionally, composites for secondary battery electrodes may be referred to as "composite for electrodes" or "composite."

[0020] <Composite for secondary battery electrodes> The electrode composite for a secondary battery contains an active material and fibrous carbon, and may further contain, optionally, a dispersant and a binder resin. The electrode composite may further contain optional components.

[0021] When the electrode composite of the present invention has a combustion temperature of the fibrous carbon in an oxygen-containing atmosphere of 520°C or less and a volume resistivity of 100 Ω·cm or less under a load of 20 kN, the fibrous carbon on the active material becomes loose and uniformly adsorbed in the composite, and a secondary battery electrode with good electrode resistance can be obtained.

[0022] The exothermic peak temperature of the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the maximum exothermic peak top (A in FIG. 1) derived from the combustion of the fibrous carbon is read and determined as the exothermic peak temperature of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even with the same type of fibrous carbon, the combustion temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.

[0023] When the combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is 520°C or lower, the fibrous carbon on the active material is adsorbed in a loose state. It is preferably 480°C or lower, and more preferably 450°C or lower. When the combustion temperature is 520°C or higher, the fibrous carbon is adsorbed in an aggregated state on the active material, so that the contact area between the active material and the fibrous carbon is small. In that case, when the composite is used as a secondary battery electrode, the electron conduction path from the fibrous carbon to the active material is reduced, leading to deterioration of the battery characteristics.

[0024] When the volume resistivity of the electrode composite for secondary batteries of the present invention is 100 Ω·cm or less under a load of 20 kN, uneven distribution of the fibrous carbon in the composite does not occur, and the electrode resistance can be effectively reduced when the composite is used as a secondary battery electrode, which is preferable. It is preferably 50 Ω·cm or less, more preferably 20 Ω·cm or less, and even more preferably 10 Ω·cm or less.

[0025] The volume resistivity of the electrode composite for secondary batteries can be determined by performing resistivity measurement based on the four-terminal four-probe method. Specifically, four needle-like probes (electrodes) are brought into contact with the composite for secondary battery electrodes to be measured, and the resistance of the test piece is calculated from the current flowing between the two outer probes and the potential difference generated between the two inner probes. The volume resistivity of the CNTs can then be calculated from the measured resistance and the thickness of the test piece. The measurement is performed using a volume resistivity measuring device (for example, the low-resistance version of the automatic powder resistivity measuring system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd.) under a load of 20 kN.

[0026] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.

[0027] As mentioned above, when the combustion temperature is 520°C or less, it indicates that the fibrous carbon in the composite is in a crushed state, and when the volume resistivity is 100 Ω·cm or less, it indicates that the fibrous carbon in the composite is not unevenly distributed and is uniformly adsorbed on the active material. By satisfying these two conditions, the fibrous carbon in the composite is crushed and is thin and uniformly adsorbed on the active material, and when it is used as an electrode for a secondary battery, it reduces the electrode resistance and favors the formation of an electronic conduction path to the active material during the battery reaction, improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, making it possible to improve the battery capacity.

[0028] <Cathode active material> The active material is a material that causes a battery reaction required to extract electrical energy. The positive electrode active material used in the positive electrode is not particularly limited. For example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used. For example, lithium manganese composite oxides (e.g., Li x Mn 2 O 4 Or Li x MnO 2), lithium nickel composite oxide (e.g. Li x NiO 2 ), lithium cobalt oxide (Li x Chief of Staff 2 ), lithium nickel cobalt composite oxide (e.g. Li x Ni 1-y Co y O 2 ), lithium manganese cobalt composite oxide (e.g. Li x Mn y Co 1-y O 2 ), lithium nickel manganese cobalt composite oxide (e.g. Li x Ni y Co z Mn 1-y-z O 2 ), spinel-type lithium manganese nickel composite oxides (e.g. Li x Mn 2-y Ni y O 4 ), lithium phosphate powder having an olivine structure (e.g., Li x FePO 4 , Li x Fe 1-y Mn y PO 4 , Li x CoPO 4 etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (e.g. V 2 O 5 , V 6 O 13 ), transition metal oxide powder such as titanium oxide, iron sulfate (Fe 2 (SO 4 ) 3 ), TiS 2, and transition metal sulfide powders such as FeS, etc. are included. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These cathode active materials can also be used alone or in combination of two or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more), tend to have a high basicity due to components derived from raw materials or elution of metal ions, and due to this effect, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.

[0029] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, and has a high aspect ratio in the long axis direction, making it easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). CNT has a shape in which planar graphite is wound into a cylindrical shape, and includes single-walled CNT, double-walled CNT, thin-layer (several layers) CNT, multi-walled CNT, and these may be mixed. Single-walled CNT has a structure in which one layer of graphite is wound. Multi-walled CNT has a structure in which two or three or more layers of graphite are wound. Also, the side wall of CNT does not have to be a graphite structure. Also, for example, CNT having a side wall with an amorphous structure is also CNT in this specification.

[0030] The shape of CNT is not limited. Such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stacking type), platelet-like (platelet), and coil-like. Among them, the shape of CNT is preferably needle-like or cylindrical tube-like. CNT may be a single shape or a combination of two or more shapes.

[0031] Examples of the form of CNT include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.

[0032] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it becomes difficult to adjust the volume resistivity to 100 Ω·cm or less. In addition, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. In addition, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.

[0033] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.

[0034] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.

[0035] <Binder resin> The composite of the present invention may contain a binder resin as necessary. The binder resin is not particularly limited as long as it is normally used as a binder resin, and can be appropriately selected according to the purpose. The binder resin used in the composite is preferably a resin capable of binding between substances such as active materials and fibrous carbon. Examples of the binder resin used in the composite include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose-based resins such as carboxymethylcellulose; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Particularly, fluororesins are preferred, such as polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), and modified products thereof. These may be used alone or in combination of two or more. Among these, from the standpoint of resistance, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, resins having these structural units, and modified products thereof are preferred.

[0036] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0037] <Method of manufacturing a composite for secondary battery electrode> The method for compounding the positive electrode active material with the fibrous carbon or the like is not particularly limited. For example, there may be mentioned a method of mixing the active material and fibrous carbon in a dry state, a method of mixing by adding a solvent, or a method of preparing a slurry and mixing in a wet state. In order to prepare a more uniform composite, a method of mixing using a dispersion liquid in which fibrous carbon or the like is dispersed in a solvent in advance is preferred. Among them, the use of a fibrous carbon dispersion is preferred because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Even if a fibrous carbon dispersion is not used, it is preferred because the same effect can be obtained by breaking up the agglomerates of the fibrous carbon using a high shear force composite machine or the like. The combination of a fibrous carbon dispersion and a high shear force composite machine is particularly preferred.

[0038] Examples of dry mixing devices include roll mills with two or three rolls, high-speed agitators such as a Henschel mixer or a Super mixer, fluid energy pulverizers such as a Micronizer or a jet mill, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro," mixers manufactured by Inoue Manufacturing Co., Ltd. such as "Planetary Mixer" and "Trimix," and mixer / granulator "High Speed ​​Mixer" manufactured by EarthTechnica Corporation.

[0039] In addition, when using a dry mixer, other raw materials such as fibrous carbon may be added directly in powder form to the active material as the base material, but in order to create a more uniform mixture, it is preferable to disperse or dissolve the other raw materials such as fibrous carbon in a small amount of solvent in advance and then mix them. Among these, the use of a fibrous carbon dispersion is preferable because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Furthermore, in order to increase the processing efficiency, it may be preferable to heat the mixture. Among dry mixers, a planetary mixer, trimix, or mechanofusion, which is capable of compounding by shearing, is preferable.

[0040] Examples of wet mixing devices include: Mixers such as dispersers, homomixers, or planetary mixers; Homogenizers such as "Clearmix" manufactured by M Techniques or "Filmix" manufactured by PRIMIX; Rotation and revolution type mixers such as THINKY's "Awatori Rentaro" Media-type dispersing machines such as a paint conditioner (manufactured by Red Devil), a ball mill, a sand mill (such as "Dyno Mill" manufactured by Shinmaru Enterprises), an attritor, a pearl mill (such as "DCP Mill" manufactured by Eirich), or a Coball mill; Wet jet mills (such as Genus PY, Sugino Machine Starburst, and Nanomizer), M-Technique Claire SS-5, and Nara Machinery Micros media-less dispersers; Other examples include, but are not limited to, roll mills, kneaders, etc. In addition, it is preferable to use a wet mixing device that has been treated to prevent metal from entering the device. When a media-type dispersing machine such as a ball mill is used, there is a risk that the structure of the active material may be destroyed by mixing, so a media-less dispersing machine is preferred.

[0041] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a dispersion medium, and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.

[0042] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 μm or more, and is preferably 5.0 μm or less, and more preferably 2.0 μm or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, making it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.

[0043] The viscosity of the fibrous carbon dispersion, measured using a B-type viscometer at 25°C and 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.

[0044] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 6 rpm measured at 25°C with a B-type viscometer by the viscosity (mPa·s) at 60 rpm. The TI value is preferably 1.0 or more and less than 10.0, more preferably 1.0 or more and less than 5.0, and even more preferably 1.0 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, dispersant, and other resin components, or the intermolecular forces thereof, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, the entanglement of the fibrous carbon, dispersant, and other resin components can be suppressed while allowing these intermolecular forces to act appropriately.

[0045] The average fiber length of the fibrous carbon in the fibrous carbon dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon in the fibrous carbon dispersion can be calculated by diluting the fibrous carbon dispersion 50 times with a non-aqueous solvent such as NMP, dropping the diluted fibrous carbon dispersion onto a substrate, drying the diluted fibrous carbon dispersion, observing the sample with a scanning electron microscope, and randomly selecting 300 pieces of fibrous carbon from the observation photograph and measuring the fiber length of each piece.

[0046] The content of the fibrous carbon is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 0.8% by mass or more, based on the total amount of the fibrous carbon dispersion. Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting it within the above range, the fibrous carbon can be present well and stably without causing sedimentation or gelation. It is more preferably 0.1 to 20% by mass, and even more preferably 0.5 to 10% by mass. Also, it is preferable that the content of the fibrous carbon is appropriately adjusted so that a fibrous carbon dispersion liquid with appropriate fluidity or viscosity is obtained depending on the specific surface area of ​​the fibrous carbon, affinity to the dispersion medium, dispersibility of the dispersant, etc.

[0047] The content of the dispersant is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 15 to 80 parts by mass, relative to 100 parts by mass of the fibrous carbon. The content of the dispersant is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass, relative to the total amount of the fibrous carbon dispersion.

[0048] The solid content of the fibrous carbon dispersion is preferably from 0.2 to 40 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %.

[0049] The fibrous carbon dispersion may be prepared by separately preparing two or more kinds of fibrous carbon having different average outer diameters and adding them to a dispersion medium. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the average outer diameter of the first fibrous carbon is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second fibrous carbon is preferably 5 nm or more and 30 nm or less, more preferably 20 nm or less. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the mass ratio of the first fibrous carbon to the second fibrous carbon is preferably 1:10 to 1:100, more preferably 1:10 to 1:50.

[0050] The average fiber length of the fibrous carbon is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a scanning electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the fiber length of each piece.

[0051] The aspect ratio is the fiber length of the fibrous carbon divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. A conductive material with a higher aspect ratio can provide higher conductivity when formed into an electrode. The aspect ratio of the fibrous carbon is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.

[0052] The specific surface area of ​​fibrous carbon is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and2 / g or less is more preferable. The specific surface area of ​​the fibrous carbon is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area of ​​the fibrous carbon are within the above ranges, a conductive path developed in the electrode is easily formed.

[0053] The carbon purity of the fibrous carbon is represented by the content (mass%) of carbon atoms in the fibrous carbon, and is preferably 80 mass% or more relative to 100 mass% of the fibrous carbon.

[0054] For the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity, fibrous carbon that has been subjected to a purification treatment may be used.

[0055] When fibrous carbon is dispersed in a disperser by collision with media such as a bead mill, or when it is repeatedly passed through a disperser over a long period of time, the fibrous carbon may be broken and short-flaked carbonaceous matter may be generated. When short-flaked carbonaceous matter is generated, the viscosity of the fibrous carbon dispersion decreases, and the gloss of the coating film obtained by coating and drying the fibrous carbon dispersion increases. Judging from these evaluation results alone, however, the short-flaked carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may worsen the resistance of the electrode. The degree of short-flaked carbonaceous matter generation can be confirmed by diluting the dispersion liquid, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, and drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion liquid so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.

[0056] The fibrous carbon may be produced by any method. The fibrous carbon can generally be produced by, but is not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method. For example, the fibrous carbon can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. The carbon source may be at least one of a hydrocarbon and an alcohol.

[0057] <Dispersant> The dispersant for the fibrous carbon dispersion is preferably one that can disperse and stabilize the fibrous carbon in the fibrous carbon dispersion. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption power to the fibrous carbon and can provide good dispersion stability. Depending on the characteristics required for dispersing the fibrous carbon, a suitable type of dispersant can be used in a suitable amount.

[0058] Examples of the resin-type dispersant that can be used include (meth)acrylic polymers, polymers derived from ethylenically unsaturated hydrocarbons, cellulose derivatives, and copolymers thereof. Examples of the polymers derived from ethylenically unsaturated hydrocarbons include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, and nitrile rubbers. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, and amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, and polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with acetal (acetoacetal-modified or butyral-modified, etc.) by aldehydes. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, ​​JP 2019-087304 A, Japanese Patent No. 6524479 A, ​​and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, homopolymer of polyacrylonitrile, copolymer of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber. Polymers in which other substituents have been introduced into a part of these polymers, modified polymers, etc. may also be used. The weight average molecular weight of the resin-type dispersant is preferably 500,000 or less, more preferably 300,000 or less, and more preferably 3,000 or more, and more preferably 5,000 or more, from the viewpoint of the balance of affinity between the dispersed substance and the dispersion medium and the resistance to the electrolyte. The resin-type dispersant may be used alone or in combination of two or more.

[0059] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, and Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Commercially available polyvinylpyrrolidone resins include, specifically, polyvinylpyrrolidone K30, K90 (manufactured by Fujifilm Wako), and K120 (manufactured by DSP Gokei Food & Chemical). Commercially available nitrile rubbers are available in various grades with different nitrile ratios, hydrogenation rates, and molecular weights under trade names such as Therban (hydrogenated nitrile rubber manufactured by Aranseo), Baymod (nitrile rubber manufactured by Aranseo), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and NipoleNBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by known synthesis methods may be used. Surfactants may be used in place of or in addition to the above-mentioned resin-type dispersants. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.

[0060] As the resin-type dispersant, a polymer containing at least an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit may be used. The aliphatic hydrocarbon structural unit of the polymer may contain an alkylene structural unit. The polymer may be hydrogenated.

[0061] The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.

[0062] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, and an alkanetetrayl structural unit. Structural units containing a branch point, such as an alkanetriyl structural unit and an alkanetetrayl structural unit, are structural units different from structural units containing a branched alkylene structure and structural units containing a branched alkyl structure, which will be described later. The aliphatic hydrocarbon structural unit preferably contains at least an alkylene structural unit.

[0063] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.

[0064] <Dispersion medium> The dispersion medium of the fibrous carbon dispersion is not particularly limited, but is preferably a high dielectric constant solvent, and preferably contains one of the high dielectric constant solvents or a mixed solvent of two or more of them. In addition, the high dielectric constant solvent may be mixed with one or more other solvents.

[0065] Examples of high dielectric constant solvents that can be used include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), water, and others such as tetrahydrofuran, urea, and acetonitrile. The dispersion medium preferably contains an amide-based organic solvent or water, and the amide-based organic solvent more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The relative dielectric constant of the high dielectric constant solvent can be a value listed in the Solvent Handbook, etc., and is preferably 2.5 or more at 20°C.

[0066] Examples of the method for removing the liquid medium and drying include hot air drying, vacuum drying, spray drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.

[0067] <Slurry for secondary battery electrode composite material> A slurry for a secondary battery electrode can be prepared using the composite for a secondary battery electrode. A composite slurry for a secondary battery electrode can be obtained by adding the composite for an electrode and a binder resin to a dispersion medium. If necessary, a fibrous carbon dispersion and other optional components may be appropriately contained within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination thereof. The optional components may be those described above for the fibrous carbon dispersion. The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material".

[0068] The solid content in the composite slurry is preferably 30% by mass or more, and more preferably 40% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 90% by mass or less, and more preferably 85% by mass or less.

[0069] The content of the electrode composite in the composite slurry is preferably 28% by mass or more, more preferably 38% by mass or more, and even more preferably 48% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 88% by mass or less, and more preferably 80% by mass or less.

[0070] The content of the binder resin in the composite slurry is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less. When the electrode composite contains a binder resin, it is preferable to adjust the total amount of the binder resin in the composite slurry to be within the above range.

[0071] The content of fibrous carbon in the composite slurry is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less. Since the electrode composite of the present invention contains fibrous carbon, it is preferable to adjust the total amount of fibrous carbon in the composite slurry to be within the above range. If it exceeds the above range, the filling amount of the active material in the electrode decreases, resulting in a low capacity of the battery. Also, if it is below the above range, the conductivity of the electrode and the battery may be insufficient.

[0072] <Method for producing secondary battery electrode composite slurry>

[0073] In the method for preparing the composite slurry, the order of adding the electrode composite and the binder resin to the dispersion medium is not particularly limited. For example, a method of preparing the binder resin by adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition; a method of preparing the electrode composite by adding the binder resin to the dispersion medium and then adding the binder resin; a method of preparing the binder resin and the electrode composite by adding them all at once to the dispersion medium, and the like can be mentioned. As a method for preparing the composite slurry, a method of adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition and performing a stirring process is preferable. The stirring device used for stirring is not particularly limited. A disperser, a homogenizer, etc. can be used as the stirring device.

[0074] <Electrode for secondary batteries> The secondary battery electrode in the present invention includes a composite for secondary battery electrodes. The electrode may further include an optional component such as a dispersant. The electrode may be formed by preparing the above-mentioned composite slurry and applying the composite slurry, or by adding a binder or the like to the composite for secondary battery electrodes without using the composite slurry and forming each component into a sheet by pressing or the like. When the composite slurry is not used, a dry mixture that has been mixed in advance or a dried product after wet mixing may be used. When the composite slurry is used, for example, the electrode film can be formed by applying the composite slurry to a current collector and removing volatiles.

[0075] <Method of manufacturing secondary battery electrodes>

[0076] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0077] The method of applying the composite slurry onto the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after application, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.

[0078] The method for dry-mixing or wet-mixing each component by adding a binder or the like to the composite for secondary battery electrode without using a composite slurry is not particularly limited, and any known method can be used. Specifically, a dry / wet disperser described in the composite preparation method can be appropriately selected.

[0079] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0080] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode and pressing each component into a sheet without using a composite slurry, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure-molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed on the current collector in advance.

[0081] Examples of the method for pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.

[0082] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least the positive electrode includes an electrode film made from the composite of the present invention.

[0083] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector. The negative electrode may be an electrode film containing a negative electrode active material formed on a current collector. The positive electrode active material may be any of the above-mentioned materials.

[0084] The negative electrode active material is not particularly limited, but may be, for example, a metal Li capable of reversibly doping or intercalating lithium ions, or an alloy thereof, a tin alloy, a silicon-based material (metal Si, Si alloy, SiO x etc.), Li X TiO 2 , Li X Fe 2 O 3 , Li X Fe3 O 4 , Li X WO 2 and other metal oxides, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can also be used alone or in combination of two or more. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials, etc.

[0085] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known ones in which ions can move can be used. For example, LiBF 4 , LiClO 4 , LiPF 6 , LiAsF 6 , LiSbF 6 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 , LiC 4 F 9 SO 3 , Li(CF 3 SO 2 ) 3 , LiI, LiBr, LiCl, LiAlCl, LiHF 2 , LiSCN, or lithium salts such as LiBPh 4 (where Ph is a phenyl group), etc. are included, but not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0086] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0087] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0088] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.

[0089] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.

[0090] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0092] <Production of Dispersant> (Production Example 1: Production of H-NBR) In a stainless steel polymerization reactor, 32 parts of acrylonitrile, 68 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.48 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3MPa, and hydrogenation reaction was carried out for 6 hours. After that, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solids were dried to obtain a dispersant (H-NBR). The Mooney viscosity (ML1+4, 100°C) of H-NBR (measured using an L-shaped rotor at a temperature of 100°C in accordance with Japanese Industrial Standard JISK6300-1) was 44. The hydrogenation rate (calculated from infrared spectroscopy by total reflection measurement method) was 0.7%. The structural unit derived from acrylonitrile determined from 1H-NMR quantitative spectrum was 32%.

[0093] In the examples and comparative examples, the following fibrous carbon was used. ·10B: JENOTUBE10B (manufactured by JEIO, multilayer CNT, average outer diameter 10 nm, specific surface area 230 m 2 / g) ·6A:JENOTUBE6A (manufactured by JEIO, multilayer CNT, average outer diameter 6nm, specific surface area 700m 2 / g)

[0094] In the examples and comparative examples, the following active materials were used. NMC: S800 (LiNi 0.8 Mn 0.1 Co 0.1 O 2 (Manufactured by Ningbo Ronbay New Energy Technology Co., Ltd.)

[0095] <Preparation of fibrous carbon dispersion> (Production Example 1) According to the materials and compositions shown in Table 1, a fibrous carbon dispersion was prepared as follows. First, NMP was placed in a stainless steel container and heated to 50°C. A dispersant was added while stirring with a disperser, and then the mixture was stirred for 1 hour to dissolve the dispersant. Next, fibrous carbon was added while stirring with a disperser, and a square-hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON). Batch dispersion was performed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. At this time, the dispersion particle size confirmed by the grind gauge was 220 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The dispersion liquid was dispersed until the viscosity at 60 rpm measured with a B-type viscometer (TOKISANGYO, VISCOMETER, MODEL: BL) was 3,000 mPa s or less. After that, a pass-type dispersion process was performed using a high-pressure homogenizer according to the number of passes shown in Table 1, and fibrous carbon dispersion 1 was obtained.

[0096] (Production Example 2) A fibrous carbon dispersion 2 was obtained in the same manner as in Production Example 1, except that the materials, composition, and number of passes were changed according to those shown in Table 1.

[0097] [Table 1]

[0098] <Electrode composite for secondary batteries> (Example 1-1) A composite for secondary battery electrodes was prepared using a high-speed mixer made by EarthTechnica Corporation according to the composition shown in Table 2. NMC and fibrous carbon dispersion 1 were mixed at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm, and then dried in an oven at 120°C for 2 hours to obtain composite 1.

[0099] (Example 1-2) According to the composition shown in Table 2, fibrous carbon dispersion 1 and solvent (NMP) were weighed out and placed in a stainless steel container, and NMC was added while stirring with a disperser, and then the mixture was stirred for 60 minutes to obtain a slurry. Using the slurry, a composite for secondary battery electrodes was produced using a spray dryer, Mini Spray Dryer B-290, manufactured by Nippon Buchi Co., Ltd. Composite 2 was obtained by spray drying the slurry at 220°C under closed system conditions (nitrogen atmosphere) using an inert loop B-295.

[0100] (Examples 1-3) A composite for secondary battery electrodes was prepared using a THINKY centrifugal mixer, Awatori Rentaro ARE-310, according to the composition shown in Table 2. The mixture of NMC and fibrous carbon dispersion 1 was stirred at 2000 rpm for 30 seconds, which was repeated four times, and then dried in an oven at 120°C for 2 hours to obtain composite 3.

[0101] (Examples 1 to 4) A composite for a secondary battery electrode was prepared using a planetary mixer according to the composition shown in Table 2. The mixture of NMC and fibrous carbon dispersion 1 was stirred at a rotation speed of 30 rpm for 30 minutes, and then dried in an oven at 120°C for 2 hours to obtain composite 4.

[0102] (Examples 1 to 5) A composite for a secondary battery electrode was prepared using a planetary mixer according to the composition shown in Table 2. Composite 5 was obtained by stirring the mixture of NMC and 10B at a rotation speed of 50 rpm for 30 minutes.

[0103] (Examples 1-6, 7, 10, and 11) Composites 6, 7, 10, and 11 were obtained in the same manner as in Examples 1-4, except that the rotation speed of the planetary mixer was changed to 50 rpm according to the compositions shown in Table 2.

[0104] (Examples 1-8, 9) Composites 8 and 9 were obtained in the same manner as in Examples 1-4, except that the rotation speed of the planetary mixer was changed to 100 rpm according to the composition shown in Table 2.

[0105] (Examples 1 to 12) A composite for secondary battery electrodes was prepared using a high-shear composite machine Mechanofusion manufactured by Hosokawa Micron Corporation according to the composition shown in Table 2. Composite 12 was obtained by stirring the mixture of NMC and 10B at a rotation speed of 3000 rpm for 10 minutes.

[0106] (Examples 1 to 13) A composite for secondary battery electrodes was produced using a high-shear composite machine Mechanofusion manufactured by Hosokawa Micron Corporation according to the composition shown in Table 2. The mixture of NMC and fibrous carbon dispersion 1 was stirred at a rotation speed of 1000 rpm for 10 minutes, and then dried in an oven at 120°C for 2 hours to obtain composite 13.

[0107] (Examples 1 to 14) Composite 14 was obtained in the same manner as in Examples 1-12, except that the rotation speed of the high-shear multifunction machine Mechanofusion manufactured by Hosokawa Micron Corporation was changed to 4000 rpm according to the composition shown in Table 2.

[0108] (Examples 1 to 15) Composite 15 was obtained in the same manner as in Examples 1-12, except that the rotation speed of the high-shear multifunction machine Mechanofusion manufactured by Hosokawa Micron Corporation was changed to 5,000 rpm according to the composition shown in Table 2.

[0109] (Examples 1-16 to 18) Composites 16 to 18 were obtained in the same manner as in Examples 1-12, except that the rotation speed of the high-shear multifunction machine Mechanofusion manufactured by Hosokawa Micron Corporation was changed to 7000 rpm according to the composition shown in Table 2.

[0110] (Examples 1-19) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 1 were weighed out into a container and stirred with a spoon for 10 minutes to obtain composite 19.

[0111] (Examples 1-20) According to the composition shown in Table 2, first, fibrous carbon dispersion 1 and an NMP solution (polyvinylidene fluoride resin: W#9300) containing 10% binder dissolved therein were weighed into a stainless steel container, and NMP was added while stirring with a disperser. The mixture was stirred for 30 minutes to prepare a dispersion solution. Next, NMC and the above dispersion solution were placed in the container of a planetary mixer and stirred at a rotation speed of 30 rpm for 60 minutes. After that, while keeping the inside of the container at 80°C with a hot water chiller, the pressure was reduced with a vacuum pump and drying was performed for 2 hours to completely remove the solvent, and a composite 20 was obtained.

[0112] (Examples 1-21) According to the composition shown in Table 2, first, the fibrous carbon dispersion 1 and the NMP solution (polyvinylidene fluoride resin: W#9300) in which 10% binder was dissolved were weighed into a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes to prepare a dispersion solution. Next, NMC and the above dispersion solution were charged into the container of a high-speed mixer, and the mixture was stirred for 60 minutes at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm. During stirring, the temperature was controlled at 25 ° C. with a temperature-controlled chiller. After that, the inside of the container was kept at 80 ° C. with a hot water chiller, and the mixture was dried for 2 hours by reducing the pressure with a vacuum pump to completely remove the solvent, and a composite 21 was obtained.

[0113] (Comparative Examples 1-1 and 1-2) According to the composition shown in Table 2, NMC and fibrous carbon (10B, 6A) were weighed out into a container and stirred with a spoon for 10 minutes to obtain composites 22 to 23.

[0114] (Comparative Example 1-3) A composite for secondary battery electrodes was prepared using a high-speed mixer made by EarthTechnica Corporation according to the composition shown in Table 2. Composite 24 was obtained by mixing NMC and 10B at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm.

[0115] The temperature of the exothermic peak and the volume resistivity were measured by the method described herein.

[0116] [Table 2]

[0117] <Preparation of positive electrode mixture slurry and positive electrode> Capacity 150cm 3 Into a plastic container, 11.25 parts of a 10% binder solution (polyvinylidene fluoride resin: W#9300) dissolved in NMP in advance and 14.85 parts of solvent (NMP) were weighed out, and then 73.9 parts of electrode composite 1 were added, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain composite slurry 1. The non-volatile content of composite slurry 1 was 75 mass%.

[0118] Composites 2 to 19 and 22 to 24 were prepared in the same manner as for composite slurry 1 to obtain composite slurries 2 to 19 and 22 to 24.

[0119] Capacity 150cm 35.62 parts of a 10% binder solution (polyvinylidene fluoride resin: W#9300) previously dissolved in NMP and 19.93 parts of a solvent (NMP) were weighed out into a plastic container, and then 74.45 parts of the electrode composite 20 were added, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain a composite slurry 20. The non-volatile content of the composite slurry 20 was 75% by mass.

[0120] The composite 21 was treated in the same manner as the composite slurry 20 to obtain a composite slurry 21.

[0121] The composite slurries 1 to 24 were applied onto aluminum foil with a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (Thank Metals, 3 t hydraulic roll press) to obtain positive electrodes 1 to 24. The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.2 g / cc.

[0122] <Assembly of a cell for evaluating the positive electrode of a lithium-ion secondary battery> The positive electrodes 1 to 24 were punched out to φ16 mm to be used as working electrodes, and metallic lithium foil (thickness 0.15 mm) was used as the counter electrode. A separator (porous polypropylene film) was inserted between the working electrode and the counter electrode, and the electrolyte (a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) was added to the positive electrodes. 6 A two-electrode sealed metal cell (Hosen HS Flat Cell) was assembled by filling it with a non-aqueous electrolyte solution in which 1M of 1M was dissolved in water. The assembly of the cell was carried out in a glove box purged with argon gas.

[0123] <Evaluation of rate characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C and a discharge end voltage of 2.5V. This operation was repeated three times, and then constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 4.2V, and constant current discharging was performed at a discharge rate of 3C and a discharge end voltage of 2.5V. 1C was the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The rate characteristic can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 0.2C discharge capacity x 100 (%) A relative value (%) was calculated based on the rate characteristic of Comparative Example 2-3, and evaluated according to the following criteria. Rate characteristic criteria ◎: 150% or more (very good) ○: 130% or more but less than 150% (Excellent) ○△: 110% or more but less than 130% (good) △: 100% or more but less than 110% (defective) ×: Less than 100% (extremely poor)

[0124] <Evaluation of cycle characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C with a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 0.2C discharge capacity to the 200th 0.2C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic = 3rd 0.2C discharge capacity / 200th 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the cycle characteristics of Comparative Example 2-3, and the cycle characteristics were evaluated according to the following criteria. ◎: 180% or more (excellent) ○: 150% or more but less than 180% (Excellent) ○△: 120% or more but less than 150% (good) △: 100% or more but less than 120% (defective) ×: Less than 100% (extremely poor)

[0125] [Table 3]

[0126] As shown in Table 3, the Examples showed superior battery characteristics compared to the Comparative Examples. Among them, Examples 2-4, 6 to 10, 14 to 18, and 20, in which the volume resistivity and heat generation peak temperature of the composite were in the most appropriate ranges, were confirmed to have superior battery characteristics. In the comparative examples, the volume resistivity and exothermic peak temperature of the composite were outside the appropriate ranges, and it is believed that the fibrous carbon aggregated and did not form a uniform composite state, leading to deterioration of the electrode resistance and battery characteristics. From the above, it was demonstrated that an electrode composite within the parameter range of the present invention can exhibit excellent battery characteristics regardless of the manufacturing method.

Claims

1. A composite for a secondary battery electrode comprising fibrous carbon and a positive electrode active material, the composite being characterized in that the exothermic peak temperature of the fibrous carbon obtained by simultaneous thermogravimetry-differential thermal analysis under an oxygen atmosphere is 520°C or less.

2. 2. The composite for a secondary battery electrode according to claim 1, wherein the composite has a volume resistivity of 100 Ω·cm or less under a load of 20 kN.

3. 3. The composite for a secondary battery electrode according to claim 1, wherein the content of the fibrous carbon is 10 mass % or less based on the mass of the composite for a secondary battery electrode.

4. 3. The composite for a secondary battery electrode according to claim 1, wherein the fibrous carbon has an exothermic peak temperature of 450° C. or lower as determined by simultaneous thermogravimetry and differential thermal analysis in an oxygen atmosphere.

5. 3. The composite for a secondary battery electrode according to claim 1, further comprising a binder resin.

6. 3. A secondary battery electrode comprising the composite for a secondary battery electrode according to claim 1 or 2.

7. A secondary battery comprising the electrode for a secondary battery according to claim 6.

8. A vehicle or device comprising the secondary battery according to claim 7.

Citation Information

Patent Citations

  • Manufacturing method of composite material for positive electrode of lithium battery

    JP2009176720A

  • Method for manufacturing a conductive material, the conductive material manufactured therefrom, and a lithium secondary battery including the same

    JP2018500713A

  • Carbon material, conductive aid, electrode for power storage device, and power storage device

    WO2020004179A1

  • Active material and battery using the same

    JP2016201228A

  • Lithium nickelate-carbon composite positive electrode active material particle powder, and manufacturing method thereof, and nonaqueous electrolyte secondary battery

    JP2017142997A